Scarcity in a time of plenty: Developing industry-university partnerships to address key challenges in the Malaysian water industry - Padfield, Rory; Richards, Cameron; Preece, Christopher (2013)
Despite the relative abundance of rainfall and plentiful surface water resources, recent reports suggest Malaysia country is faced with the prospect of water scarcity.The predicted scarcity is less related to changes in rainfall patterns but in the diminishing availability of water resources and treatment capacity for urban populations, both of which are linked to the inadequacy of the current water management regime.Further to this, growing concerns over dilapidated infrastructure (i.e. non-revenue water as high as 40 percent in some cities), urban water pollution concerns, institutional weaknesses, and political interference to the implementation of recent water reforms have sought to characterize Malaysia's modern day water industry.One way of addressing the current unsustainability of the water industry is for greater collaboration and partnership between the industry's key players, including developing robust and relevant industry-university collaborative partnerships.To date, there is no evidence of a strategy to coordinate and integrate broad interests of industry and university stakeholders; instead, research tends to be done in an an hoc manner, focused on specific technical issues without addressing some of the more fundamental and complex industry challenges.With this in mind, this paper aims to present the findings of a recent research project aimed at developing an interdisciplinary research framework for industry-university collaboration in the Malaysian water industry.